Implementation of English Medium Instruction (EMI) and Its Influence on Improving Students' English Skills in Joint Degree Class of D4 Nautical Study Program of Politeknik Maritim Negeri Indonesia - Marselia , Marselia; Rahindra Bayu Kumara; Sutantyo, Erwin (Universitas PGRI Adi Buana Surabaya, 2025)
The purpose of this study is exploring the implementation of English Medium Instruction (EMI) and Its Influence on Improving Students' English Skills in Joint Degree Class of D4 Nautical Study Program of Politeknik Maritim Negeri Indonesia. It especially aims to 1) explore the implementation of EMI in the Joint Degree class of Nautical Study Program; 2) examine the lecturers’ and students’ perceptions of using English as the medium of instruction, and 3) describe the impact of EMI on enhancing students’ English proficiency. This study is a descriptive qualitative which focuses on analysing how EMI is implemented in Joint degree class and also to find out how the teacher and students perceive the use of EMI in classroom, afterward it is going to explain the consequences of EMI on improving students' English skills. This study presents several findings based on the research questions raised. 1) English has not been widely used in the Joint Degree program. This is primarily because many of the lecturers in the program have admitted to lack confidence in speaking English. The low level of English proficiency among the lecturers is one of the factors contributing to their reluctance to teach English; 2) there is a correlation between students’ perception and the consequences of using English in the classroom, 3) For the majority of students, the use of English as the medium of instruction impacts their English language skills. This encourages them to review the material presented in both languages, thereby indirectly allowing them to learn English. They are also motivated to be more active and to study to improve their English skills, as they consider this very important, especially in preparation for attending lectures in Germany. Some recommendations are drawn in order to make the use of English as medium of instruction can be implemented well in Joint Degree class such as to prepare the class better as the add value of the school quality, provide professional development for lecturers, and foster a welcoming atmosphere where the students feel at ease practicing English, motivating them to engage in conversations, even if it begin in the simple way.